Bilateral Involvement in Developmental Dislocation of the Hip: Analysis of 561 Patients Operated on Using the Limited Posteromedial Approach - Batuhan Gencer; Özgür Doğan; Ali Biçimoğlu (MDPI AG, 2023)
Our objective was to scrutinize the risk factors related to bilateral involvement in the developmental dysplasia of the hip (DDH) and to inspect the impact of bilaterality on the enduring results of the DDH. All patients, aged between 6 and 18 months, who underwent surgery using the limited posteromedial approach (734 hips from 561 patients), were included in this study. The number of births, birth type, history of consanguineous marriage, family history, and swaddling were analyzed. Physical examination and complaints of the patients were evaluated, and direct radiographs were examined in terms of the redislocation, avascular necrosis, and residual acetabular dysplasia. Among the 561 patients, bilateral DDH was observed in 173 patients (30.8%). The use of swaddling was found to be statistically significant between groups (p = 0.012). The use of swaddling for more than one month was associated with a higher odds ratio for bilaterality (p = 0.001, OR = 1.56, 95% CI: 1.2-2.0). Furthermore, bilaterality was associated with a higher risk for redislocation in DDH (p = 0.001, OR = 4.25, 95% CI: 1.6-11.2). The study concludes that swaddling for over a month is strongly linked with the bilateral involvement in DDH. It is important to note that bilaterality plays a crucial role in the development of redislocation after open reduction in DDH.